Online me Filipino teenagers' use of entertainment forums on Pinoyexchange.com for self-presentation and impression formation - Yamzon, Elisha P. 1990-
"This study aimed to find out how Filipino teenagers used entertainment forums on the website PinoyExchange.com to present themselves and how they form impressions. This research revealed how exposed the members of PinoyExchange.com are and other factors regarding online self-presentation and impression formation. A background on the process of how teenagers came to find online discussion boards as a venue for self-presentation and impression formation is discussed in the literature review. Joseph Walther's Hyperpersonal Model of Computer-Mediated Communication and Erving Goffman's Theory of Self-Presentation are used as framework for the study. Important concepts such as selective self-presentation and idealized impressions are provided by the two theories to guide the study. The researcher used online methods, such as online survey and online focus interviews, to explain self-presentation and impression formation first-hand from teenage forum members of PinoyExchange.com. The study found out that Filipino teenage members of PinoyExchange.com forums are active and are highly exposed to the website. They form impressions through other members' posts and their impressions are often idealized."